MECHANICAL PROPERTIES OF RECYCLED AGGREGATE CONCRETE WITH STEEL FIBER: A REVIEW - Ashtar S. Al-Luhybi (Tikrit Journal of Engineering Sciences, 2019)
In the building process, the recycling of aggregates arising from building and demolition debris is one of the best alternatives to maintain the environment and the areas needed to bury these debris. It also helps to preserve natural concrete sources from depletion efficiently. The use of recycled aggregates in new concrete manufacturing, however, leads to a decrease in concrete's strength characteristics. This reduction rises with the rise in the percentage of recycled aggregates used in concrete, which has caused many researchers to undertake many researches on how to enhance the characteristics of recycled aggregate-containing concrete. This paper presents several studies that examined the effect of adding steel fiber to improve the properties of concrete containing a coarse recycled aggregate.